Les sexualités des mineurs sous le contrôle du juge pénal aux XIXe et XXe siècles - Hélène Duffuler-Vialle (Criminocorpus)
The analysis of article 334 is particularly rich. First, the principles of individual and sexual freedoms of the 19th century were only theoretical, which is reflected in the formal analysis of the law. Moreover, as doctrine, legislators and, to a lesser extent, case law systematically point out, it is less a question of defending sexual freedom than of defending the family institution by refusing to violate the honour of families through legal proceedings. The legislator claims to limit article 334 to only one very specific case: pimping, but at the same time, in the drafting of the law, the terms chosen are particularly obscure. Just as the regulation of prostitution has been delegated to the local public authority, the legislator wanted to delegate control of sexualities to judges. The various legislative reforms confirmed that the legislator did not want to take up the subject and on the contrary wanted to leave all power in this matter to the criminal judge, despite the legal uncertainty in which litigants found themselves due to the unpredictability of case law. Faced with the very great power left to it, the Court of Cassation nevertheless occasionally rejected this role of censor, and refused in particular to distinguish between homosexuality and heterosexuality. It also refused to criminalize any form of sexuality of minors. Faced with this partial resistance from the judges, the Vichy laws have redrawn the boundaries between licit and illicit sexuality. Moreover, the construction of the judicial reasoning with regard to article 334 is particularly interesting. It's never about the child, it's about sexuality. In child sexuality, what the judge is interested in is to moralize sexuality and not to protect the child. The minority is only a pretext for setting sexual rules. Indeed, as the criminalists point out, the damage is irrelevant, it is the offender's behaviour that interests the judge. The legal reasoning never concerns the consequences of the offence on the child. Finally, this analysis of article 334 of the Criminal Code perfectly supports the realistic theory of interpretation developed by the professor of public law and legal philosopher Michel Troper. Indeed, the interpretation made by the judge is not a choice but a decision, which the judge conceals by invoking the law. The judge here is clearly a legislator. The judge's reasoning is imbued with emotion and the litigant is in a situation of total legal uncertainty, since the judge creates the law when he applies it, as shown by the jurisprudential chaos of the application of article 334 and the legal fictions used to justify the decisions.